Christianizing the Roman empire (A.D. 100-400) - MacMullen, Ramsay, 1928- (New Haven, CN Yale UP, 1984)
Includes bibliographical references and indexes.
Keywords: Evangelistic work -- history -- early church, ca. 30-600.